FEATURES OF DISTANCE EDUCATION AT THE OTOLARYNGOLOGY, HEAD AND NECK SURGERY DEPARTMENT - Herych, O. M.; Popovych, V. I.; Orishchak, D. T.; Koshel, I. V.; Vasylіuk N. V.; Herych, P. R.; Orishchak, O. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Quality education is the key to the country’s future, essential to its national identity and welfare. In the modern labor market, the requirements for professional competencies of graduates are growing. This situation led to new forms and higher education methods aimed at creating a comprehensive continuing education system and expanding the scope of independent student work that will form self-organization skills and self-education [1,2]. Distance learning is a purposeful process of interaction between teacher and student, based on the use of modern information and telecommunication technologies that allow distance learning, which is relevant in today’s conditions. [3,4,5,6]. The widespread of distance learning is not accidental. It is a natural development stage and education adaptation to current conditions [7,8]. The introduction of distance learning at the Department of Otorhinolaryngology, Head and Neck Surgery is an important part of education in higher medical schools in current conditions. Otorhinolaryngology is a clinical discipline, so the learning process cannot be carried out in distance learning based only on test control and oral answer. Thus, teachers should use quality illustrative material and modern resources such as the School of Evidence-Based Medicine, the Academy of Otorhinolaryngology "Eurolor", Ivano-Frankivsk School of Otolaryngology, to motivate students to study and think logically using clinical information and medical knowledge to solve complex clinical problems. Those resources have many videos of clinical cases with real patients, comments during the process of clinical examination and chosen treatment strategy, and in the case of surgical treatment, demonstration of all stages of the surgical procedure from the operating room. Our work aimed to improve the quality of distance learning by systematizing the acquired knowledge and professional skills based on the principles of evidence-based medicine.